2022
DOI: 10.1093/cdn/nzac053.059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Perceived Stress and Sleep Improvement With the Dairy Bioactive Lactium®

Abstract: Objectives To evaluate Lactium® perceived effectiveness in reducing symptoms related to stress and anxiety, a consumer study has been performed. The satisfaction data has been objectivize using scientific validated questionnaires. Methods This consumer study has been performed in three countries: France (n = 122), USA (n = 111) and China (n = 105) with subjects suffering of moderate stress and sleep disorders. Lactium® 300 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Two safety indices were assessed during the examination visit and again 8 weeks after the intervention. Moreover, to overcome the uncertainty of treatment efficacy, the intervention period of this study was set to 8 weeks, at least twice as long as that used in previous studies ( 17 , 19 , 24 ) that investigated the short-term efficacy of the product. In addition, a study period of more than 8 weeks was established according to a previously-completed comparative study on Lactium and L-theanin ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two safety indices were assessed during the examination visit and again 8 weeks after the intervention. Moreover, to overcome the uncertainty of treatment efficacy, the intervention period of this study was set to 8 weeks, at least twice as long as that used in previous studies ( 17 , 19 , 24 ) that investigated the short-term efficacy of the product. In addition, a study period of more than 8 weeks was established according to a previously-completed comparative study on Lactium and L-theanin ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Objective assessments of actigraphy indices revealed more significant increases in sleep efficiency and overall sleep quality in the experimental group than that in the control group ( 17 , 18 ). Moreover, a multinational study reported significant improvements in stress levels and sleep quality within 1 month after supplementation with Lactium ® , with 80% of the participants reporting satisfaction with its effects ( 19 ). L-theanine, chemically known as gamma-glutamyl ethyl amide, is a unique non-protein amino acid that was first discovered in green tea in the mid-20th century.…”
Section: Introductionmentioning
confidence: 99%